New inflammatory markers for prediction of non-dipper blood pressure pattern in patients with essential hypertension: Serum YKL-40/Chitinase 3-like protein 1 levels and echocardiographic epicardial adipose tissue thickness. (18th August 2015) - Bakirci, Eftal Murat; Degirmenci, Husnu; Hamur, Hikmet; Gunay, Murat; Gulhan, Barıs; Aydin, Merve; Kucuksu, Zafer; Ceyhun, Gokhan; Topal, Ergun
Abstract: The aim of the present study was to investigate whether YKL-40 levels and epicardial adipose tissue (EAT) thickness were associated with non-dipping pattern in essential hypertension (HT). Age- and sex-matched 40 dipper hypertensive patients and 40 non-dipper hypertensive patients were included in the study. Non-dippers had significantly increased EAT thickness and higher YKL-40 and high-sensitivity C-reactive protein levels than dippers. Multivariate logistic regression analysis showed that the EAT thickness and serum levels of YKL-40 and high-sensitivity C-reactive protein were independent predictors of non-dipping pattern in essential HT. In essential HT, presence of non-dipping pattern is associated with increased inflammatory response.